2016
DOI: 10.1177/1077558716659022
|View full text |Cite
|
Sign up to set email alerts
|

Physician Assistant and Nurse Practitioner Malpractice Trends

Abstract: Trends in malpractice awards and adverse actions (e.g., revocation of provider license) following an act or omission constituting medical error or negligence were examined. The National Practitioner Data Bank was used to compare rates of malpractice reports and adverse actions for physicians, physician assistants (PAs), and nurse practitioners (NPs). During 2005 through 2014, there ranged from 11.2 to 19.0 malpractice payment reports per 1,000 physicians, 1.4 to 2.4 per 1,000 PAs, and 1.1 to 1.4 per 1,000 NPs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 16 publications
3
33
1
Order By: Relevance
“…One of our psychiatrist informants in North Carolina reported that acting as the supervising physician for a group of PMHNPs put him into a higher risk group and increased his malpractice insurance premiums, which represents a cost to the physician supervisor. We found this surprising since the rate of malpractice payment reports against NPs is only about 10% of those for physicians (Brock et al, 2017).…”
Section: Excessive Supervision Requirements Increase Health Care Costmentioning
confidence: 80%
“…One of our psychiatrist informants in North Carolina reported that acting as the supervising physician for a group of PMHNPs put him into a higher risk group and increased his malpractice insurance premiums, which represents a cost to the physician supervisor. We found this surprising since the rate of malpractice payment reports against NPs is only about 10% of those for physicians (Brock et al, 2017).…”
Section: Excessive Supervision Requirements Increase Health Care Costmentioning
confidence: 80%
“…Our results with regard to the amount of indemnity paid on behalf of various providers build on previous work. 9,14 Brock et al used the National Practitioner Data Bank to determine the rate over time that PAs, nurse practitioners, and physicians incurred: (1) claims that were paid on their behalf and (2) licensure adverse actions. 9 Of paid claims, our median indemnity of ∼$192,000 that was paid on behalf of physicians was consistent with Brock et al's report of $195,000, the latter of which was normalized to 2014 valuation and projected to decline based on the slope of previous years of data.…”
Section: Discussionmentioning
confidence: 99%
“…9,14 Brock et al used the National Practitioner Data Bank to determine the rate over time that PAs, nurse practitioners, and physicians incurred: (1) claims that were paid on their behalf and (2) licensure adverse actions. 9 Of paid claims, our median indemnity of ∼$192,000 that was paid on behalf of physicians was consistent with Brock et al's report of $195,000, the latter of which was normalized to 2014 valuation and projected to decline based on the slope of previous years of data. 9 However, our median indemnity of ∼$353,000 that was paid on behalf of PAs and ∼$57,000 that was paid on behalf of APRNs differed from Brock et al's report of $125,000 and $130,000, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malpractice study discusses the empirical evidence liability risk of malpractice impact in doctor diagnostic imaging (Li & Brantley, 2015), most often focuses on tabulation and comparison of claims by type of service providers (Brock, Nicholson, & Hooker, 2016;Miller, 2013;Miller, 2012;Miller, 2011), identifying the causes of frequent allegations resulting from diagnosis (Miller, 2013;Miller, 2012;Miller, 2011); Doctors have higher claims rates than assistants and nurses (Brock Nicholson, & Hooker, 2016;Leigh & Flynn, 2013); doctor disciplinary action in practice (Brock Nicholson, & Hooker, 2016;Leigh & Flynn, 2013;Balestra, 2013).…”
Section: Introductionmentioning
confidence: 99%